Height outcome of short children with hypochondroplasia after recombinant human growth hormone treatment: a meta-analysis. (November 2015) - Massart, Francesco; Miccoli, Mario; Baggiani, Angelo; Bertelloni, Silvano
Hypochondroplasia (HCH) is a genetic skeletal dysplasia, characterized by rhizomelic short height (Ht) with facial dysmorphology and lumbar hyperlordosis. Albeit there are concerns that HCH children may not achieve optimal long-term outcome in response to recombinant human growth hormone (rhGH), anecdotal experiences suggested at least short-term Ht improvement. After thorough search of published studies, meta-analysis of rhGH use in HCH children was performed. In 113 HCH children, rhGH administration (median 0.25 mg/kg/week) progressively improved Ht pattern with 12 months catch-up growth (p < 0.0001). Then, Ht improvement resulted constant until 36 months (p < 0.0001), but stature remained subnormal. While bone age chronologically progressed, no serious adverse events were reported. In conclusion, our meta-analysis indicates that rhGH treatment progressively improved Ht outcome of HCH subjects.